WhatsApp Analyzer: A Tool to Measure the User Performance in Social Platform - Jena, Amrut Ranjan; Kumar, Pratyush; Islam, Rafiqul (International Journal of Computer Sciences and Engineering, 2026)
An application called WhatsApp has emerged as the most popular and effective means of communication in recent years. The heroku web application called WhatsApp Chat analyzer provides analysis of WhatsApp groups. In this paper authors applied matplotlib, streamlit, seaborn, re, pandas, and certain NLP concepts for analyzing WhatsApp chart. Here authors combine machine learning with NLP. This WhatsApp conversation analyzer imports a user's WhatsApp chat file, analyses it, and produces various visualizations as a consequence